Chinese Art and Technology Industry Development - Yao, Jun; Han, Dong (Opción, 2019)
The research aims to investigate the development of the Chinese culture and technology sector via intelligence, descriptive, analytical and content analysis. As a result, cultural development and technological progress can be designed and accelerated to a certain extent. Large-scale restructuring of economic geography within and outside the country is becoming a decisive factor for the modern state. In conclusion, Huge investment in the scientific activities of domestic scientists and the popularization of culture contribute to China’s leadership in the development of art and modern technology.